IMPLEMENTASI STRATEGI KOMUNIKASI ORGANISASI UNTUK MENINGKATKAN MUTU LAYANAN PENDIDIKAN DI SMK - Muhammad Dahlan; Hendro Widodo; Dian Hidayati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the implementation of organizational communication strategies in improving the quality of educational services in Vocational High Schools (SMK). The study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation studies with school leaders, teachers, and education personnel. Data were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that organizational communication strategies in vocational high schools are implemented through a combination of formal and informal two-way communication. This communication plays a crucial role in strengthening work coordination, enhancing teacher professionalism, streamlining educational services, and encouraging improvements in the quality of learning. However, the implementation of organizational communication strategies still faces obstacles such as differences in individual character, differing perceptions of policies, and the sudden delivery of online information that lacks direct explanation. Solutions implemented include leadership introspection, an adaptive communication approach, strengthening two-way discussion forums, and evaluating the effectiveness of the communication media used. This study concludes that an open, participatory, and well-managed organizational communication strategy is a key factor in improving the quality of educational services in vocational high schools.